THE EFFECT OF WORK DISCIPLINE AND INFRASTRUCTURE ON EMPLOYEE PERFORMANCE AT THE REGIONAL DISASTER MANAGEMENT AGENCY OF LAMPUNG PROVINCE - Refi Arioen; Maria Elina (University of Sang Bumi Ruwa Jurai, 2022)
This type of research is quantitative research with the sample used in this study amounted to 33 employees who were selected randomly. Data collection methods include primary data and secondary data. Data collection techniques include observation, documentation and questionnaires. The data analysis method uses a quantitative approach with the help of the SPSS Windows version of the statistical tool. 18.0 includes the calculation of the validity test, reliability test, regression test, coefficient of determination test t test, and F test.The results of testing the hypothesis of the effect of work discipline on employee performance partially show that work discipline has a positive effect on employee performance with a contribution of 32.4%. The effect of infrastructure on employee performance partially shows that infrastructure has a positive effect on employee performance with a contribution of 26.8%. Simultaneous hypothesis testing shows that the independent variables of work discipline and infrastructure together have a positive effect on the dependent variable, namely performance with a contribution of 51.3%, while the remaining 48.7% is a variation of other variables not examined in this study.